The Role of ATRX in Glioma Biology - Nandakumar, Pravanya; Mansouri, Alireza; Das, Sunit (Frontiers in Oncology, 2017)
The current WHO classification of CNS tumors has made a tremendous leap from past editions by incorporating molecular criteria in addition to the pre-existing histological parameters. The revised version has had a particular impact on the classification of diffuse low grade gliomas and their high grade variants. The ATRX status is one of the critical markers that define the molecular classification of gliomas. In this review, we will first provide an overview of the role of ATRX in regular cell biology. Further, the role of ATRX in tumorigenesis, specifically gliomas, is comprehensively elucidated. The possible correlation of ATRX status with other genetic/epigenetic modifications is also presented. We conclude by discussing some of the challenges associated with incorporating ATRX status assessment into routine clinical practice while also exploring opportunities for future diagnostics/therapeutics in gliomas based on ATRX status.